2015
DOI: 10.2147/cpt.s41760
|View full text |Cite
|
Sign up to set email alerts
|

Sleep electroencephalography as a biomarker in depression

Abstract: Abstract:The sleep electroencephalogram (EEG) provides biomarkers of depression, which may help with diagnosis, prediction of therapy response, and prognosis in the treatment of depression. In patients with depression, characteristic sleep EEG changes include impaired sleep continuity, disinhibition of rapid-eye-movement (REM) sleep, and impaired non-REM sleep. Most antidepressants suppress REM sleep in depressed patients, healthy volunteers, and in animal models. REM suppression appears to be an important, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 126 publications
0
6
1
1
Order By: Relevance
“…Actually, biomarker properties of HRV in REM sleep did resemble REM density. The latter is considered a trait marker of MDD, with high values indicating increased risk of depression (review: Steiger et al, 2015). In our study, both, HRV and REM density separated between patients (total group at week 1 and 4; responders and non-responders at week 4) and matched controls but they did not predict response.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Actually, biomarker properties of HRV in REM sleep did resemble REM density. The latter is considered a trait marker of MDD, with high values indicating increased risk of depression (review: Steiger et al, 2015). In our study, both, HRV and REM density separated between patients (total group at week 1 and 4; responders and non-responders at week 4) and matched controls but they did not predict response.…”
Section: Discussioncontrasting
confidence: 52%
“…Accordingly, we compared HRV in REM sleep with previously established REM sleep-derived biomarkers of depression, such as REM density and cordance. Elevated REM density (a measure of rapid eye movement frequency during REM sleep) is an endophenotype of depression (Lauer et al, 1995;Modell et al, 2005;Steiger et al, 2015), and indicates an increased risk of depression recurrence (Hatzinger et al, 2004). Further, in a sub-sample of this study population, we have previously shown that the quantitative electroencephalography (QEEG) biomarker cordance could predict antidepressant treatment response in MDD patients.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…This pattern points to a reciprocal interaction between sleep architecture and hormones of the hypothalamic-pituitary-somatotrophic (HPS) and HPA systems. Confirming the sleep-promoting role of GHRH and the sleep-disrupting effect of CRH, in older adults the typical age-related reduction in GH levels is accompanied by reduced SWS, whereas in both older adults and in depressed younger adults increased CRH levels contribute to the typically-observed sleep disruptions (27,42).…”
Section: Endogenous Hpa Hormones and Their Effect On Sleepmentioning
confidence: 85%
“…Objective sleep markers in depressed patients concern sleep disturbances such as prolonged sleep latency (SL), increased wake after sleep onset (WASO), increased early morning wake time, decreased total sleep time (TST), decreased sleep efficiency (SE = percentage of sleep on the total bed time), decreased slow waves sleep (SWS), decreased REM sleep latency, increased REM amount [30]. Nevertheless, mood disorders are also commonly found in patients affected by sleep disorders (i.e.…”
Section: Introductionmentioning
confidence: 99%